Perlindungan Hukum Pemegang Tanah Bekas Milik Adat Perorangan (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
The purpose of this study is to analyze how the form of legal protection is given to holders of former customary land after the entry into force of Article 96 PP. 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration (hereinafter referred to as PP. No. 18/2021), wherein the provisions of Article 96 it is explained that written evidence of land formerly owned by custom (Petuk Tax Earth/Landrente, girik, pipil. Ketitir and Indonesian verponding) which are owned by individuals must be registered within 5 (five) years since the provisions of the Government Regulations are passed and in the event that the 5 (five) years period expires, written evidence of land formerly owned by custom is declared invalid and cannot be used as a means of proving the registration of land rights. The type of research used is normative legal research using statutory and conceptual approaches. Through this research, researchers offer preventive legal protections for holders of former customary land with a rights recognitions mechanism, in which the mechanism for recognizing this right is carried out by the applicant/owner of the former customary land by making a statement of physical ownership of the former customary land, made with at least 2 (two) witnesses, where later the statement letter was used as the basis for land registrations, as well as researchers offering repressive legal protection to former customary landholder by conducting a judicial review to on the PP. No. 18/2021.